Examination of surface and material properties of nanostructural oxide coatings for joint total and module replacement arthroplasty - Zykova, Anna; Safonov, Vladimir; Smolik, Jerzy; Rogowska, Renata; Lukyanchenko, Volodimir; Samoilenko, Olexsandr; Donkov, Nikolai; Kolesnikov, Dmitrii; Goncharov, Igor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Deposition of functional coatings on metal substra- tes (stainless steel 1H18N9, titanium alloy Ti6Al4V) makes it possible to combine biocompatibility of ceramics with advantages of metals for improving tribological characteristics of prostheses and creating new low-cost and innovative prototypes for defect replacement in patients of different age groups. The specific properties of nanostructural oxide coatings make them most promising for subsequent applications in implantology. High hardness parameters up to 9 Gpa, adhesion strength up to 40 N and a low friction coefficient with a strong tendency to decrease in fluids (0.07) were estimated. The corrosion test results show that oxide coating deposition had improved the corrosion resistance parameters by a factor of ten both for stainless steel and titanium substrates. The surface with oxide coatings demonstrated electrical inertness and capacitive properties. The hydrophilic property of coated surfaces versus the metal one was investigated by the method of tensiometry. Surfaces with nanostructural oxide coatings demonstrated improved biocompatibility due to dielectric properties and high values of surface energy.